(untitled) (Journal of Economic Research & Business Administration, 2017)
The paper contribute to the research regarding the effectiveness of Islamic banking in Kazakhstan. The comparative analysis of Islamic Banking and Conventional Banking firmsis made. Moreover, it touch the differences of the Islamic Banks and Conventional Banks in terms of historical origin, mobilizing of financial resources, and ways of generating profit, operating principles, and equity structure. Methodological base of research in given clause was made with modern concepts Islamic banking and Islamic model of financing adequacy, asset quality, management, earnings and liquidity as a whole. Findings of the results indicate the mathematical model consists of a probability space, a Brownian motion and a Poisson process. The jumps are independent and identically distributed. The approach consists of defining a notion of risk and production instrument asset quality in order to minimize the risk. To empirically evaluate performance of the banks, different financial ratios are employed which are based on CAMEL framework during the period 2011-2015. We measure performance in terms of capital adequacy, asset quality, management, earnings and liquidity. In this work, descriptive statistics, one-way Annova and regression analysis are used to make hypothesis test and determine the ratio significance. Consequently, results from empirical analysis indicate that there is difference in profitability determinants.